Counter Discourse on the Idea of Islamic State and Formalization of Religion in the Qur’anic Exegesis of KH. Abdurahman Wahid - Rafif, Ahmad Ahnaf (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
This research discusses KH Abdurrahman Wahid’s Qur’anic interpretation written in his articles around the 2002–2003 period. Initial studies of the text show that Gus Dur was only active in elaborating the Qur’anic verses in his articles after he stepped down from the president and Chairman of the PBNU. This initial observation then raised questions regarding his lack of interpretation during Orde Baru (New Order), primarily when he served as Chairman of PBNU. Thus, what context finally made Gus Dur want to include the interpretation of the Qur’an in his article? This paper answers these questions using a descriptive-interpretive method. The theory used is the critical discourse analysis by Teun A. Van Dijk, which contains three steps, namely text analysis, personal and social cognition, and context. Furthermore, the results reveal that: (1) there is a discourse contest in the democratic transition period between those who are pro with an Islamic state and those against it; (2) Gus Dur positioned himself as a party against the idea of an Islamic state. It happened when Gus Dur used the verses of the Qur’an to strengthen his argument; (3) Gus Dur’s interpretation which prioritizes the principle of humanity and can reach a wider audience, has implications indirectly for the development of the interpretation of the Qur’an in Indonesia.